PENDIDIKAN SEKSUAL SEJAK DINI PADA ANAK - Rachmawati, Dian; Nurhidayah, S. Psi., M.Si, Siti (LPPM Universitas Islam 45 Bekasi, 2020)
Sexual education is a clear and correct information regarding the issue of human sexuality which includes knowledge of conception, pregnancy, and the birth of sexual behavior which is properly given and related to the norms prevailing in society. This Community Service aims to provide knowledge for children to know personal areas that must be protected from others and children can protect themselves from the crimes that are around them by refusing from behaviors that are not liked by children such as saying